Changes in Skin Colour and other Related Quality Characteristics of 'B10' Carambola (Averrhoa Carambola L.) at Different Stages of Maturity - Irsan, Mukhlis (1998)
A study was conducted on changes in skin colour and other related quality characteristics of 'B10' carambola (Averrhoa carambola L.) at different stages of maturity. In Experiment I the carambola were harvested at different stages of maturity beginning from 57 to 93 days after fruit-set with three day intervals between each harvest. Skin colour (L*, a*, b*, C* and h' values), chlorophyll and carotenoid contents of the fruit were determined at each stage of maturity. In Experiment II other related quality characteristics such as flesh firmness, soluble solids concentration, sugar (sucrose, fructose, and glucose), ascorbic acid and organic acid (malic, citric and oxalic) contents at nine colour indices (as had been categorised in Experiment I) were also determined. Respiration rate and ethylene production of carambola were determined to study the climacteric nature of the fruit. Each of the experiment was conducted using a completely randomised design and the data obtained were analysed using analysis of variance and Duncan Multiple Range Test. Simple regression model was used to determine relationship between maturity stages and skin colour (Experiment I) and relationship between colour indices and other related quality characteristics (Experiment IT). Correlations among parameters in each experiment were obtained by means of Pearson's correlation matrix.